The Effect of Green Purchase Intentions on Intention to Buy Environmentally Friendly Straws in Batam City - Pradnia Adella; Listia Nurjanah (eCo-Buss, 2022)
In recent years, the use of environmentally friendly straws has become a lifestyle trend, one of which is stainless steel straws which are the most popular new innovations today with the advantages of being used multiple times and environmentally friendly functions. Along with the development of technology, new innovations in environmentally friendly straw materials have emerged, such as paper, glass, metal, ice, and cake materials. The purpose of this study was to determine the relationship between attitude towards green products, green perceived value, green perceived risk, green trust and green purchase intentions in Batam City. This research method is a comparative causal research. The object of this research is environmentally friendly straws, i.e. stainless steel, bamboo, paper, glass, and silicone. Data collected using a questionnaire distributed to 231 respondents with the consideration that male and female respondents who have used environmentally friendly straws in Batam used the accidental sampling method. SEM-PLS 3.0 is applied for data processing. Based on the results of the study, attitude towards green products provides an important role for green purchase intentions, as well as green perceived value and green trust. Meanwhile, green perceived risk has a negative effect on green purchase intentions.